Topography of Fear and Violence in Ahmad Al Sadawi's Frankenstein in Baghdad - Hameed Mankhi, Azhar; Muhammed Nati, Ikhlas (مجلة كلية التربية, 2019)
This paper examines the postcolonial Iraqi novel which gives a voice to the Iraqi writers to describe for the first time the political repression and violence in Iraq before and after the US invasion.  They   address the bad conditions in Iraq after the 2003 and discuss the reshaping of the Iraqi identity due to the sectarian conflicts that have endangers the minority population in this pluralistic society. We intend to stress the contemporary fears of Iraqi people through the use of the monster.  In this paper, the researchers attempt to present a new voice in the Iraqi novel that was silenced for a long time. The Iraqi writers tend to describe aesthetically the terrible national condition in Iraq post 2003.